2017
DOI: 10.1016/j.ijheatmasstransfer.2017.07.117
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of turbulent forced convection of nanofluid in channels with cylindrical and spherical hollows

Abstract: Experimental study of forced turbulent convection of water-based nanofluids with nanoparticles of zirconium oxide (ZrO2) was carried out in smooth tubes and channels with wall heat transfer enhancers. Nanopowders with average particle size of 44 and 105 nm were used in the experiments. The Reynolds number ranged from 3000 to 8000. It is revealed that the increments in the heat transfer coefficient and the pressure drop when using nanofluids depend on the surface shape of the channel. It is shown that nanofluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Minakov et al [16] carried out experimental study of forced turbulent convection of water-based nanofluids with nanoparticles of zirconium oxide (ZrO2) in smooth tubes and channels with wall heat transfer enhancers. Nanopowders with average particle size of 44 and 105 nm were used in the experiments.…”
Section: Nanofluid Flowsmentioning
confidence: 99%
“…Minakov et al [16] carried out experimental study of forced turbulent convection of water-based nanofluids with nanoparticles of zirconium oxide (ZrO2) in smooth tubes and channels with wall heat transfer enhancers. Nanopowders with average particle size of 44 and 105 nm were used in the experiments.…”
Section: Nanofluid Flowsmentioning
confidence: 99%
“…Minakov et al 126 have calculated the hydrodynamic length (lh) for stabilization in the tube using Equation (33). They have concluded that for 44 nm‐sized ZrO 2 ‐water nanofluids, the HT enhancement ( h ) is increased by 35% and for 105 nm‐sized ZrO 2 ‐water nanofluids, the HT enhancement ( h ) is decreased by 20% compared to pure water at a fixed Re number.…”
Section: Forced Convective Heat Transfermentioning
confidence: 99%
“…Similar observation also was found by Zainal Abidin et al [87] and Abdullah et al [3] however for different types of nanofluids. Furthermore, Minakov et al [88] evaluated the heat transfer performance of ZrO2/water nanofluids for 4.0% volume concentrations with different nanoparticle sizes of 44 and 105 nm. The experiment was undertaken for Reynolds number of 3,000 to 8,000 and different types of tubes viz.…”
Section: Other Types Of Oxide Nanofluidsmentioning
confidence: 99%